The Shift and Continuity of Japanese Defense Policy: Revolutionary Enough? - Santoso, Ria Putri; Perwita, Anak Agung Banyu (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2016)
The security environment in East Asia has continuously evolved, particularly, China’s maritime expansion and DPRK’s provocative behavior. Japan, with its military being limited by its Peace Constitution, has been steadily shifting its defense policy to respond to its strategic environment for the past three of its Prime Ministers: Naoto Kan, Yoshihiko Noda, and Shinzo Abe. Historical enmities, military capability, as well as territorial disputes have increased the threats of Japan’s neighbors to Tokyo’s national security. Since 2010, Japan has established a National Defense Program Guideline (NDPG), shifted its defense strategy from the Basic Defence Force (kibanteki boei ryoko) to Dynamic Defense Force (doeki boei ryoko), revised its Three Principles on Arms Exports, created the National Security Council (NSC), the National Security Strategy (NSS), and the Medium Term Defense Program (MDTP), and revised its article 9 of its Peace Constitution. While the NSC, NSS, MDTP, and article 9 are under the Abe administration, the claim that the steps Abe have undertaken to be revolutionary is in fact, a continuity from his predecessors despite coming from opposing political backgrounds. Despite of several significant changes in its defense policy, Japan still abides to its Constitution and its military is still limited.